PREVALENCE AND DETERMINANTS OF PROTEINURIA IN TYPE 2 DIABETES MELLITUS - ., Dimple; Arora, Vineet; Arora, Mohit; Kaur, Parminder; Arora, Anterpreet Kaur (Pakistan Journal of Physiology, 2015)
Diabetic nephropathy is a leading cause of end stage kidney disease among type 2 diabetics. Proteinuria has been noted to be the cardinal symptom of progressive loss of renal function. This study examined the impact of duration of diabetes, demography (age, gender) and metabolic factors on the frequency of proteinuria among type 2 diabetic patients. Methods: One hundred and forty-four patients suffering from the disease were examined clinically after taking a detailed history and investigated for the study parameters. Results: Maximum number of patients (40.3%) were in the age group of 60–69 years followed by 33.3% in age group of 50–59 years with mean age 59.7 years. Duration of diagnosed disease in 46.5% patients was 1–5 years and 36.8% had duration of 6–10 years, 9.8% had duration between 11–15 years, and 6.9% were less than one year. The mean duration was 6.13 years. The numbers of associated complications were high, 40.3% cases were having hypertension, 33.3% had neuropathy and 10.4% had associated ischaemic heart disease. Proteinuria was seen in 36.10% patients; 16.66% had mild proteinuria, and 19.44% had neuropathy. Conclusion: Proteinuria is seen in more than one third of diabetic patients, predominantly males, and the risk of nephropathy increases with duration of disease.